A self management plan in the treatment of adult asthma. Issue 3 (March 1989) - Beasley, R; Cushley, M; Holgate, S T
Abstract : To determine whether routine assessment of peak expiratory flow (PEF) in association with a self management plan based on inhaled corticosteroid use is effective in the management of chronic asthma, 36 consecutive adult patients with asthma attending an outpatient chest clinic were admitted to an open prospective study. Patients were treated with inhaled salbutamol and beclomethasone dipropionate in an attempt to achieve normal lung function. Each patient had a "potential normal value, " which was either the predicted normal or the maximum PEF value achieved by the patient, whichever was the higher. Patients measured PEF at home and if it fell by more than 30% from the potential normal value the dose of beclomethasone was doubled until PEF returned to the potential normal value, then continued at 20 mg/day for the same number of days. If PEF fell to below 150-200 l/min patients were asked to obtain emergency medical assistance. In the 30 patients who completed the trial the six months before and the six months after intervention with the self management plan were compared. There was a substantial improvement in both subjective and objective measurements of asthma severity, with a significant reduction in nights woken, days lost from work, and requirement for oral corticosteroids and a significant increase in baseline lung function. Routine measurement of PEF in association with a self management plan appears to be effective in reducing symptoms of asthma and improving lung function.